Social, demographic and economic profile of maize growers’ households: empirical evidence from Sussundenga District, Mozambique (Research, Society and Development, 2022)
This study aimed to describe the socio demographic and economic characteristics of maize growers’ households in Sussundenga district, Mozambique. Data were collected by applying questionnaire to 140 maize growers and four focus group meetings with these farmers between February and March, 2018. After collection, data were analyzed using descriptive statistics. The results show that although the majority of the population in the district is female, maize grower’s households are mostly male-headed. There was an inverse relationship between age and school level of the households heads. Compared to men, women are less educated and less involved in activities other than agriculture. Most households have low income per capita. Although many households practice off-farm activities, agriculture remains an important economic activity. Households grow a wide range of crops, with maize being the most important. Market failures limit the willingness of households to produce this crop with market-oriented. In this sense, actions to reduce market failures can be crucial for farmers to make the most of maize production.